2018
DOI: 10.1007/s13205-018-1473-y
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of crop productivity through interventions of omics technologies in India: challenges and opportunities

Abstract: With the continuous increase in the population of developing countries and decline of natural resources, there is an urgent need to qualitatively and quantitatively augment crop productivity by using new tools and technologies for improvement of agriculturally important traits. The new scientific and technological omics-based approaches have enabled us to deal with several issues and challenges faced by modern agricultural system and provided us novel opportunities for ensuring food and nutritional security. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 224 publications
0
7
0
Order By: Relevance
“…The results of present study also revealed that these genes might be not expressed during developing spikes stage. Transcriptome of an organism varies over time and depends upon several factors, including stage of development and environmental conditions (Pathak et al 2018).…”
Section: Genome-wide Identification Of Ros-scavenging Genes In Finger Milletmentioning
confidence: 99%
“…The results of present study also revealed that these genes might be not expressed during developing spikes stage. Transcriptome of an organism varies over time and depends upon several factors, including stage of development and environmental conditions (Pathak et al 2018).…”
Section: Genome-wide Identification Of Ros-scavenging Genes In Finger Milletmentioning
confidence: 99%
“…The omics era has taught us to follow a holistic approach while interpreting the complex biological systems starting from molecular to cellular level ( Pathak et al, 2018 ). As the cost of the omics analyses continues to decrease, different high-throughput omics data are made available.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…By contrast, Asia had the one of the highest malnourishment rates in the world (11.4%) but with high pesticide use rates (3.64 kg/ha). Despite the possibilities of manipulating bacterial communities for more sustainable bioremediation processes, the very concept of omics introduces several problems: they are more expensive and complex approaches than the traditional analyses and require more powerful bioinformatics systems to analyze the large amounts of data generated ( Pathak et al., 2018 ). Without help to implement and fund omic technologies, developing agricultural countries will have greater problems in achieving self-sufficiency to solve problems of environment.…”
Section: Bacterial Xenobiotic Responses By Omics-based Approaches Andmentioning
confidence: 99%